Przekłady literatury macedońskiej na język polski i polskiej na język macedoński za 2015 rok - Dembowska, Zofia (Przekłady Literatur Słowiańskich, 2016)
Polish-Macedonian and Macedonian -Polish literary translations in 2015 This commentary conserns the reasons and motivation for choosing particular novels to be translated into Macedonian. A short review of their style is given, as well as the common ground with the Macedonian literature. We describe the way of the working of the publishing houses which have decided to publish Polish literature. Problems in translation turn out to be of a cultural nature, concerning the differences and, as a result, the reader is presented with the picture of contemporary Polish society, which is overwhelmed by critical thinking, but still deals with the history as a way to further develop the tradition. Key words: Polish-Macedonian translations, Macedonian-Polish translations, translation commentary, Polish literature, Macedonian literature